Analysis of The Big-Five Personality and Knowladge to Healthy Life Motivation With SEM PLS - Rasminto Rasminto; Nadiroh Nadiroh; Yufiarti Yufiarti (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
This research proved the effectiveness of the big-five personality factors and knowledge of reproductive health to motivation to live healthy on students of public high school. The method used was a survey with a partial least square (PLS) with 279 samples participated through purposive sampling. Some instruments have been measured, namely the healthy life motivation(reliability 0.971), the big-five personality (reliability 0.937), and knowledge about reproductive health (reliability 0.874). The research data was carried out by PLS. The results showed that; 1) there is a positive and significant relationship between big-five personality and motivation healthy living, although controlled by the second order correlation; 2) there is a negative and significant relationship between knowledge about Kespro and motivation to live healthy, although controlled by the second order correlation; and 3) there is a positive relationship and significant between big-five personality and knowledge about Kespro together with motivation to live healthy. And also from the five big-five personality factors, it shows that the strongest contribution to healthy living motivation is extraversion and agreeableness. Therefore, it can be concluded that if the motivation to live a healthy life is to be increased, then the big-five personality and knowledge of Kespro must be considered.